Artificial Intelligence Techniques for Machining Performance: a Review - M. M., Rahman; K., Kadirgama; M. M., Noor (2010)

(untitled)
This paper reviews the approaches of artificial neural network (ANN) on machining performance. ANN considered as a successful approach to modelling the machining process for predicting performance measures through the development of an expert system. An expert system is an interactive intelligence program with an expert-like performance in solving a particular type of problem using knowledge base, inference engine and user interface. The approaches of ANN in past years with respect to cutting forces, surface roughness of the machined work piece, tool wear and material removal rate were reviewed. Results from literatures indicated that the ANN has the ability in generalizing the system characteristics by predicting values close to the actual measured ones.